Designing for Engagement: The Role of Interactive Elements in Public Art Sculptures in Shanghai - Zhao, Zhan; Liu, Duanduan; Fan, Xu (Journal of Ecohumanism, 2024)
Public art in urban landscapes are significant as they play a cultural role for both beautifying and reflecting cultural identity. Traditional public sculptures, catch our eye but quickly fade from cognitive due to passive experience. However, currently, pubic art are integrated with interactive elements such as touch, visuals, sound etc. to enhance perception. Thus, this study aims to i) To explore how public art sculptures can be designed to foster interaction and engagement with the public. ii) To investigates the role of interactive elements in sculptures, such as movement, touch, and multimedia components, and their effectiveness in creating meaningful public experiences. This study adopted a mixed method involving survey of 100 partcipants through online platform and four case studies. Following analysis, it was found that the physical, visual, auditory, and digital interactions contribute uniquely to the engagement of public. Though the study was limited due to its participant selection, it laid a foundation for understanding the designing elements of public art.